The dual role of circHIPK3 in cancer and its implications for multiple drugs resistance: a systematic review and computational approach - Campelo, Marcelo Monteiro; Reis-das-Mercês, Laís; Vidal, Amanda Ferreira; da Silva, Felipe Rodolfo Pereira; de Oliveira, Ana Carolina Alves; Monteiro, José Rogério de Souza; Cabral, Caique Guimarães; Noronha, Renata Coelho Rodrigues; Pereira, Adenilson Leão (Frontiers in Oncology, 2025)
BackgroundcircHIPK3 role in cancer as oncogene or tumor suppressor is still debated, therefore, this study aimed to understand the dual role of this circRNA in different cancers. Furthermore, all available evidence of circHIPK3 interactions with sponged-miRNA and RBPs in oncological diseases were systematically gathered to better understand the its functional role in cancer.MethodsPubMed, BioMedCentral, Web of Science, Embase and Scopus databases were searched for articles published until October 2024, following the PRISMA guideline. In computational analysis, miRNAs’ sponged target genes and RBPs were used for gene enrichment in KEGG, REACTOME and Gene Ontology, and TISSUES expression. miRTargetLink 2.0 was used to search for target genes, and STRING v.12.0 for gene enrichment.ResultscircHIPK3 can regulate 33 miRNAs which regulate 399 target genes, and that were mainly enriched in major biological pathways important for cancer development and promoting. circHIPK3/miR-124-3p/miR-637/miR-338-3p are the most well documented interactions in cancers that may control MAPK, Jak/STAT3, Wnt/β-catenin, and PI3K/Akt signaling pathways. circHIPK3 regulates miRNAs that modulate genes responsible for chemoresistance, such as ATP-binding cassette and solute carrier transporters genes, and DNA repair genes. circHIPK3 has binding sites for RBPs, which participate mainly of RNA processing and control, and gene expression regulation. Finally, we believe that it has an onco-circRNA role in most cancers, except in bladder cancer, where it has a TS-circRNA function likely due to the microenvironment permeated by high amounts of hydrogen peroxide.ConclusioncircHIPK3 dysregulation is an important mechanism for cancer establishment, progression and chemoresistance making it an interesting molecule with a potential therapeutic target.